2022
DOI: 10.1039/d1nj05634d
|View full text |Cite
|
Sign up to set email alerts
|

Development of poly(vinyl alcohol)/chitosan/aloe vera gel electrospun composite nanofibers as a novel sorbent for thin-film micro-extraction of pesticides in water and food samples followed by HPLC-UV analysis

Abstract: Herein, a novel composite of poly(vinyl alcohol) (PVA)/citric acid (CA)/ chitosan (CS)/ aloe vera gel (AV) was fabricated via the electrospinning technique followed by a thermal treatment. The resultant composite...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…It has been reported that there are many applications in bioactive coatings for food packaging 181 , fish packaging 192 , meat packaging [193][194][195] and fruit packaging 171 . In terms of plasticity and mechanical properties, polyvinyl alcohol-based sensitive detection agents or probiotics can effectively detect food and effectively package sensitive active substances, which have been reported in intelligent food packaging [196][197][198] .…”
Section: Polyvinyl Alcoholmentioning
confidence: 99%
“…It has been reported that there are many applications in bioactive coatings for food packaging 181 , fish packaging 192 , meat packaging [193][194][195] and fruit packaging 171 . In terms of plasticity and mechanical properties, polyvinyl alcohol-based sensitive detection agents or probiotics can effectively detect food and effectively package sensitive active substances, which have been reported in intelligent food packaging [196][197][198] .…”
Section: Polyvinyl Alcoholmentioning
confidence: 99%
“…Pesticide residues pose a significant threat not only to non-target organisms but also to the overall ecology of soil and water [83][84][85]. Therefore, conducting tests for pesticide residues in soil, water, and food is crucial for mitigating potential health risks [86,87]. However, analyzing trace amounts of polar contaminants accurately in samples, owing to the complexity of the matrix and the low concentration of the target analytes, has long been a challenging and critical area in separation techniques.…”
Section: Ils As Solventmentioning
confidence: 99%
“…9,10 Currently, micro-solid-phase extraction techniques have attracted considerable attention due to their ease of setup, exceptional efficiency, rapidity, and minimal adsorbent and solvent usage. 11 Consequently, micro-solid phase extractionpipette tip (PT-SPE) has emerged as a modern, cost-effective, rapid, effective, and environmentally friendly method for preconcentrating diverse analytes including drugs, peptides, and proteins. [12][13][14] In the PT-SPE technique, the amount of adsorbents applied in the pipette tip and the use of harmful organic solvents are significantly reduced.…”
Section: Introductionmentioning
confidence: 99%